SEMI-MARKOV MODEL OF THE AIRCRAFT EQUIPMENT OPERATION - Ліннік, О. (Science-based technologies, 2012)
The matters of the use of semi-Markov aircraft models were considered in this article. The problem of adequate consideration of all possible states of the aviation technique, affecting the development of effective maintenance program was also discussed.